Understanding Emotions in Policy Studies through Foucault and Deleuze - Anna Durnová (Politics and Governance, 2018)
Discussing Foucault’s and Deleuze’s work on meaning-making, the article argues that we might make better use of the intersubjectivity of a meaning when interpreting emotions. Interpreting emotions in texts remains complicated because discussion on the ontological character of emotions sustains an opposition of emotion to meaning structures. Both Foucault and Deleuze conceive meaning-making through permanent oscillation between the subjective accounts of a meaning and its collective interpretation. These two dimensions are not in conflict but create meaning through their interdependence. On the basis of this interdependence, we can conceive of an interpretive analysis of emotions as a way to study language means that label particular emotions as relevant, legitimized, or useful. This shift of the debate on emotions away from what emotions are and toward what they mean enhances the critical shape of interpretive analysis of emotions because it uncovers conflicts hidden behind the veil of allegedly neutral policy instruments.